2010
DOI: 10.15288/jsad.2010.71.674
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Craving Criterion in DSM Alcohol Use Disorders

Abstract: ABSTRACT. Objective: Adding a craving criterion-presently in the International Classifi cation of Diseases, 10th Revision, diagnosis of alcohol dependence-has been under consideration as one possible improvement to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), and was recently proposed for inclusion by the DSM Substance-Related Disorders Work Group in the Fifth Revision of diagnostic criteria for alcohol use disorders. To inform cross-cultural applicability of this modifi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 21 publications
5
46
1
Order By: Relevance
“…There has been a long debate about the symptom of craving in the context of addictive disorders [53,54]. In the field of addictive-like eating, craving has been found as one mediator for specific types of foods, BMI, and binge episodes [55].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a long debate about the symptom of craving in the context of addictive disorders [53,54]. In the field of addictive-like eating, craving has been found as one mediator for specific types of foods, BMI, and binge episodes [55].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the addition of craving was supported indirectly by findings from behavioral (Heinz et al, 2009;Miller & Goldsmith, 2001;Waters et al, 2004), imaging, pharmacology (O'Brien, 2005, and genetics research (Agrawal et al, 2013;Foroud et al, 2007). Findings from IRT studies (Cherpitel et al, 2010;Hasin et al, 2012;Keyes et al, 2011;Mewton et al, 2011) showed equivocal psychometric benefit from adding this criterion. However, from a clinical perspective, some (O'Brien, 2005;Tiffany & Wray, 2012) but not all (Munafò & Hitsman, 2010;Perkins, 2009) investigators view craving as key to an SUD diagnosis and its reduction as central to treatment.…”
Section: Cross-substance Revisionsmentioning
confidence: 98%
“…As reported by nearly a quarter of all current alcohol users (Cherpitel et al, 2010), this totals 11 criteria (O’Brien, 2010). There is the need to explore the applicability of this new diagnosis in different populations and countries (Mewton et al, 2011; Borges et al, 2010; Shmulewitz et al, 2010), including urban populations in middle-income countries such as Brazil, the largest country in Latin America with approximately 190 million inhabitants (The World Bank, 2013).…”
Section: Introductionmentioning
confidence: 99%